Transformation of jealousy in romantic relationships and its catalysts in digital age - O. G. Shchukina (Вестник университета)
The article studies the process of jealousy transformation in romantic relationships under the influence of digitalization. The author considers such definitions as “digital jealousy”, “digital infidelity”, and “virtual sex”, formulates a definition of digital jealousy, and considers emotional and behavioral reactions when experiencing jealousy under the influence of events and factors of the digital environment. Based on the content analysis results, behavioral markers that can be considered by a partner as evidence of digital infidelity and/or cause digital jealousy have been identified. The specific characteristics of digital jealousy include its existence in conditions of quasi-reality, diffusiveness, deployment in time and space, alienation from the fact of physical infidelity, and virtual representation. The author notes the connection between the intensity of the digital jealousy experience and the subjective significance of virtual space and representation in it. Ambivalence of the digital jealousy experience is expressed by the perception of its occurrence, on the one hand, as a predictor of physical infidelity, and, on the other hand, as a manifestation of crisis in romantic relationships and emotional estrangement of partners. It has been revealed that jealousy in digital space is largely due to a sense of ownership in relation to the time and attention of a partner and is associated with general transformation of romantic relationships in modern society.